A spring-mass system with elastomeric beams and stretchable interconnects. (8th December 2017) - Yang, Zining; Potekin, Randi; Vakakis, Alexander F; Kim, Seok
Abstract: This paper presents a design construct of a spring-mass system involving a silicon seismic mass, elastomeric beams, and stretchable metallic interconnects which exhibits a mechanical strain-based tunable spring constant and resonance. Serpentine-shaped metallic conductors are encapsulated in polyimide to form the electrical interconnects, which are then integrated on a microfabricated silicon seismic mass with elastomeric beams. The interconnected beam undergoes a nearly 93% elongation with high electrical conductance before failure, which benefits microelectromechanical systems (MEMS) devices requiring large deflection and reliable signal transmission simultaneously. Moreover, the experimental results show that the spring constant of the beams increases by more than a factor of four under 30% axial strain. The tunable resonant frequency of the spring-mass system is also characterized, showing that the resonant frequency changes from 85–155 Hz when a 10% axial strain is applied to the beams. Because of these unique tunable mechanical properties, the presented design construct of the spring-mass system serves as a platform for potential applications including soft MEMS sensors and vibration energy harvesters especially for low frequency and broadband ambient vibration sources.